EFEITO DO ÃCIDO BÃ“RICO SOBRE ð˜Šð˜¦ð˜³ð˜¢ð˜µð˜ªð˜µð˜ªð˜´ ð˜¤ð˜¢ð˜±ð˜ªð˜µð˜¢ð˜µð˜¢ (WIED, 1824) (DIPTERA: TEPHRITIDAE), EM CONDIÃ‡Ã•ES DE LABORATÃ“RIO - Potenza, Marcos Roberto; Raga, Adalton; Sato, MÃ¡rio Eidi; Souza Filho, Miguel Francisco de (REVISTA DE AGRICULTURA, 2020)
EFEITO DO ÃCIDO BÃ“RICO SOBRE ð˜Šð˜¦ð˜³ð˜¢ð˜µð˜ªð˜µð˜ªð˜´ ð˜¤ð˜¢ð˜±ð˜ªð˜µð˜¢ð˜µð˜¢ (WIED, 1824) (DIPTERA: TEPHRITIDAE), EM CONDIÃ‡Ã•ES DE LABORATÃ“RIO